Loss of superconductivity with the addition of Al to MgB2 and a structural transition in Mg1-x AlxB2. - Slusky, J; Rogado, N; Regan, K; Hayward, M; Khalifah, P; He, T; Inumaru, K; Loureiro, S; Haas, M; Zandbergen, H; Cava, R (2001)
The basic magnetic and electronic properties of most binary compounds have been well known for decades. The recent discovery of superconductivity at 39 K in the simple binary ceramic compound magnesium diboride, MgB2, was therefore surprising. Indeed, this material has been known and structurally characterized since the mid 1950s (ref. 2), and is readily available from chemical suppliers (it is commonly used as a starting material for chemical metathesis reactions). Here we show that the addition of electrons to MgB2, through partial substitution of Al for Mg, results in the loss of superconductivity. Associated with the Al substitution is a subtle but distinct structural transition, reflected in the partial collapse of the spacing between boron layers near an Al content of 10 per cent. This indicates that superconducting MgB2 is poised very near a structural instability at slightly higher electron concentrations.